(untitled) (CAHIERS MAGELLANES-NS, 2024)
TADs have become increasingly popular in the orthodontic sector latest years as they reduce patient compliance requirements while increasing the number of treatment alternatives to better meet esthetic and occlusal treatment goals. Mini-implants obtain anchorage from jawbone, which increases control over orthodontic tooth movement and helps minimize side effects when treating misaligned teeth. There is little research on micro-screws, and the majority of them indicate that dental students are unaware of them. Aim: The aim of this study was to measure the level of knowledge about orthodontic mini screws among dental students in Saudi Arabia. Materials and Methods: This study uses a structured questionnaire that the authors created as part of a cross-sectional study. The population of this study consists of Saudi dental students (male and female) from all six years of study and seventh year of internship in all dental colleges in Saudi Arabia. The Qualtrics calculator was used for estimating the sample size. The survey was used to gather information from students via Google Form and was then sent around various dental student groups. Those who answered the questionnaire during 2023-2024 AD were selected as participants in our study. Results: 59.6%, exhibit a low level of knowledge and awareness in this area, while 37.7% demonstrate a moderate level. However, 2.7% of students possess a high level of understanding. There is also statistically significant relation to the level of education (p value= 0.002). Conclusion: This study gave us insights about the knowledge associated with the use of orthodontic TADs among the dental students. There is overall low level of knowledge (60%) as regard mini-implants among dental students. Thus, introducing the topic of TADs earlier in the undergraduate dental program will enhance the students’ case-based learning setup. Hence, the early exposure to use of TADs will improve the students’ clinical problem-solving and decision-making skills during their undergraduate clinical years.